Perancangan Interior Museum Indonesia Raptor Center Kota Surabaya - Hartono, Andi (Intra, 2015)
Mankind increasingly thirsts to explore about what nature has at the present time. For example, Indonesian in the entire regions keep rare animal species which are protected by the government, the birds of prey. Raptor Club Indonesia is an organization that concerns with the fate of birds of prey in the country, and contributes to the conservation of birds of prey. To support the activities of Raptor Club Indonesia, the Indonesian Raptor Center is proposed to aid education, information, history, conservation and rehabilitation of birds of prey which have been taken from illegal trading and illegal pet. People from overseas supports the initiative to set up Indonesias Raptor Center, in the hope that it can sensitize the people of Indonesia. The interior design presentation with knowledge, quality and adequate facilities is required to support these activities. Indonesian Raptor Center will be the only center of knowledge and conservation of birds of prey in Indonesia.